Evaluation of Mechanical Properties of Samples Printed by FDM Method - Linda, Miloslav; Muller, Miroslav; Choteborsky, Rostislav (Manufacturing Technology Journal, 2014)
To ensure optimal conditions of instruction in technical subjects it is fundamental to have laboratory trainings where students learn methods of the material measuring and they get pieces of knowledge about a test equipment. Financial cost of samples leads to minimizing laboratory trainings. It can be solved by fused deposition modelling (FDM). The aim of the research was to test a possibility to use test samples made by means of FDM method for an implementation within the practical training. Within the research two standard materials determined for FDM (that means ABS plastic and PLA) were used. Test samples were made / printed by a printer EASY3DMAKER with using a software G3DMAKER. Test of an abrasive wear, a hardness Shore D measurement, a tensile strength and an impact strength were performed for verifying a functionality of the test samples printed by FDM method for laboratory experiments.
Keywords: laboratory training; testing; research; fused deposition modeling